Culture or Psychosis: A Social Behavior that Prompts a Psychopathology or a Psychopathology that Prompts a Social Behavior? - Corzo Pérez, Paula Ariadna (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2013)
The aim of this review is to illustrate through a case tried, the difficulties encountered while dealing with patients’ special cultures and beliefs, which require a culture assessment, given its special features. Also, this review aims at providing basic tools for understanding and analyzing the impact of the cultural environment. In the event that a health professional stands in front of cross culture context in his daily practice, one in which magical and spiritual elements dominate, he/she must have the ability to assess it in a scientifically, way but without interfering with the cultural belief of the individuals. The F44.3 The Trance and Possession Disorder (9) was included in the 1999 International Classification of Diseases (ICD-10) of the World Health Organization for epidemiological and planning purposes. However, this inclusion is not sufficient to describe the complexity of the behaviors and thought patterns related to all different culture beliefs.